Plant hormone cytokinin at the crossroads of stress priming and control of photosynthesis - Hudeček, Martin; Nožková, Vladimíra; Plíhalová, Lucie; Plíhal, Ondřej (Frontiers in Plant Science, 2023)
To cope with biotic and abiotic stress conditions, land plants have evolved several levels of protection, including delicate defense mechanisms to respond to changes in the environment. The benefits of inducible defense responses can be further augmented by defense priming, which allows plants to respond to much lower levels of stimulus faster and more robustly than plants in the naïve (non-primed) state. Priming provides a low-cost protection of agriculturally important plants in a relatively safe and effective manner. Many different organic and inorganic compounds have been successfully tested to induce resistance in plants. Among the plethora of commonly used physicochemical techniques, priming by plant growth regulators (phytohormones and their derivatives) appears to be a viable approach with a wide range of applications. While several classes of plant hormones have been exploited in agriculture with promising results, much less attention has been paid to cytokinin, a major plant hormone involved in many biological processes including the regulation of photosynthesis. Cytokinins have been long known to be involved in the regulation of chlorophyll metabolism, among other functions, and are responsible for delaying the onset of senescence. A comprehensive overview of the possible mechanisms of the cytokinin-primed defense or stress-related responses, especially those related to photosynthesis, should provide more insight into some of the less understood aspects of this important group of plant growth regulators.